The Impact of Digital Transformation on Economic Growth in Developing Countries: A Case Study of Indonesia - Sutomo, Deni Anggreani (Universitas Pahlawan Tuanku Tambusai, 2025)
Digital transformation has become a pivotal force in reshaping economic structures and accelerating growth, particularly in developing countries. This study examines the impact of digital transformation on Indonesia’s economic growth by analyzing key indicators such as internet penetration, mobile cellular subscriptions, digital infrastructure, and e-government services. As a lower-middle-income country with one of the largest digital economies in Southeast Asia, Indonesia offers a relevant case for understanding how digitalization contributes to macroeconomic performance. Using a quantitative approach and time-series data from 2000 to 2023, this research applies regression analysis to assess the relationship between digital transformation variables and Indonesia’s real Gross Domestic Product (GDP). The findings reveal that increased internet usage and digital infrastructure development significantly contribute to economic growth. Moreover, improvements in e-government initiatives and broader mobile connectivity also show a positive correlation with national productivity. This study contributes to the growing body of literature on digital economics by presenting empirical evidence from Indonesia and providing a contextualized analysis for other developing economies facing similar challenges in digital adoption. The results underscore the urgency for policymakers to invest in inclusive digital infrastructure, promote digital literacy, and address regional disparities in technology access. Given the transformative power of digital tools, accelerating digital adoption can serve as a strategic lever for sustainable development and economic resilience in the post-pandemic era.